Molecular mechanism of LIP05 derived from Monascus purpureus YJX-8 for synthesizing fatty acid ethyl esters under aqueous phase - Zhao, Jingrong; Xu, Youqiang; Lu, Hongyun; Zhao, Dong; Zheng, Jia; Lin, Mengwei; Liang, Xin; Ding, Ze; Dong, Wenqi; Yang, Maochen; Li, Weiwei; Zhang, Chengnan; et al. (Frontiers in Microbiology, 2023)
Fatty acid ethyl esters are important flavor chemicals in strong-flavor Baijiu. Monascus purpureus YJX-8 is recognized as an important microorganism for ester synthesis in the fermentation process. Enzyme LIP05 from YJX-8 can efficiently catalyze the synthesis of fatty acid ethyl esters under aqueous phase, but the key catalytic sites affecting esterification were unclear. The present work combined homology modeling, molecular dynamics simulation, molecular docking and site-directed mutation to analyze the catalytic mechanism of LIP05. Protein structure modeling indicated LIP05 belonged to α/β fold hydrolase, contained a lid domain and a core catalytic pocket with conserved catalytic triad Ser150-His215-Asp202, and the oxyanion hole composed of Gly73 and Thr74. Ile30 and Leu37 of the lid domain were found to affect substrate specificity. The π-bond stacking between Tyr116 and Tyr149 played an important role in stabilizing the catalytic active center of LIP05. Tyr116 and Ile204 determined the substrate spectrum by composing the substrate-entrance channel. Residues Leu83, Ile204, Ile211 and Leu216 were involved in forming the hydrophobic substrate-binding pocket through steric hindrance and hydrophobic interaction. The catalytic mechanism for esterification in aqueous phase of LIP05 was proposed and provided a reference for clarifying the synthesis of fatty acid ethyl esters during the fermentation process of strong-flavor Baijiu.